KARAKTERISTIK MIKROKAPSUL ANTOSIANIN UBI JALAR UNGU DENGAN TEKNIK SPRAY DRYING - Anting Wulandari, Titi Candra Sunarti, Farah Fahma, Erliza Noor (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
Anthocyanin is a source of natural dyes that can replace synthetic dyes. Its nature which is susceptible to certain environmental conditions limits its usefulness in food processing, so it is necessary to encapsulate it in a matrix in the form of microencapsulation. Anthocyanin was extracted from purple sweet potato. Encapsulation was carried out by spray drying technique with the matrix carboxymethyl starch (CMS) and sodium alginate. The matrix combinations used were 1% CMS, CMS-alginate (0.75%: 0.25%), and CMS-alginate (0.5%: 0.5%). The aim of this work was to obtain the physical and morphological characteristics of purple sweet potato anthocyanin microcapsules in each matrix combination. The results of the purple sweet potato anthocyanin micro encapsulation using spray dyring technique showed that microcapsules with CMS matrix of 1% had the highest efficiency encapsulation (EE) and yield of 99.37 ± 0.49% and 58.52 ± 0.23% respectively. Purple sweet potato anthocyanin microcapsules with CMS 1% matrix gave the best thermal stability compared to CMS-alginate matrix (0.5% : 0.5%) and CMS-alginate (0.75% : 0.25%). The average particle size for purple sweet potato anthocyanin microcapsules from various matrices ranged from 4.2-4.8 µm with a rounded shape.Keywords: anthocyanin, microcapsule, CMS, alginate, spray drying